Empire and decapitation: A postcolonial re-reading of the story of John the Baptist - Dube, Zorodzai (Verbum et ecclesia, 2025)
Under what conditions does the Empire decapitate its subjects? The gospel of Mark 6:18–29 shares with the other synoptic gospels (Matthew 14:3–12; Luke 9:7–9) the most gruesome murder – the decapitation of John the Baptist. Using a postcolonial optic, this article has the following tasks: firstly, looking into the ways the story has been framed by the redactor and, secondly, accenting the hegemonic presence and role of the Roman Empire and its insatiable desire for power under the false pretext of peace – pax romana. Given that imperial practices of control, power, violence and murder are common throughout history, the article reinterprets the decapitation of John as a typical postcolonial narrative that illuminates and sheds light on the imperial practice of decapitation and its treatment of subjects in general. By juxtaposing the practices of the Roman Empire during the 1st-century Palestinian region to that of African colonial settings, the article argues that the decapitation of John fits into typical patterns of hegemony and control by imperial and colonial regimes.Intradisciplinary and/or interdisciplinary implicationsThis article contributes to comparing practices of decapitation in antiquity with colonial practices of hegemony and control.